Kajian Bentuk Dan Makna Tata Rias Pengantin Jungpara Padukan Khas Jepara Jawa Tengah - Nur Puji Yanti; Dewi Lutfiati; Biyan Yesi Wilujeng; Sri Usodoningtyas (Universitas Negeri Surabaya, 2025)
This research aims to determine 1) the history of Jungpara Padukan bridal makeup 2) the form and meaning of facial makeup 3) hair styling 4) clothing 5) accessories. The research method uses a qualitative descriptive approach. Data collection techniques are interviews, observations, and documentation. Data analysis in this study using source triangulation techniques. Research Results 1) The history of Jungpara Padukan bridal makeup comes from the old name of the Jepara area as makeup inspired by the geographical conditions, plantations and female figures of Jepara. 2) Orange red eyeshadow means courage, nanggal sepisan eyebrows mean positive, red chili lip color. Jungpara bridal makeup depicts elegance and courage. 3) hair styling the geger bulus bun is circular and means unity in family life. 4) The bride's attire includes a red velvet kebaya meaning courage with a yellow Jepara elung jarit (noble), red (courage), green (fertility) and orange (self-confidence). The groom's attire is sikepan meaning courage, a Jepara elung motif jarit and velvet pants meaning a cover for the genitals. 5) The head accessories used by the bride are; pilis meaning calm, oklo giri spiritual and the real world, oklo kluwung meaning water element of life, tusuk konde Queen Kalinyamat meaning courage, Jebahan, ronce melati and keket melati meaning of rights, obligations and responsibilities household life. Brooches in the form of rawis flowers three levels, first level means the courage of Queen Kalinyamat, the second level Queen Shima and the third level is a depiction of R.A Kartini. The groom's accessories include udheng enlightenment of thought patterns, clothing accessories include kerset necklace bond of relationship with God, tosan aji meaning strength and Selop meaning readiness.Keywords: make-up, form and meaning, Jepara, Jungpara